Legal Protection for Consumers Receiving Defective Products in Online Transactions - Purnaningrum, Sageta; Roisah, Kholis (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
Legal protection for consumers receiving defective products in online transactions is critically needed due to the surge in e‑commerce, which has led to increased consumer complaints particularly regarding product quality and authenticity. Consumers often face urgency when encountering unclear seller identities and inadequate product information, resulting in financial losses from receiving defective goods. This situation underscores the necessity of legal accountability for producers and sellers and highlights the need for a robust framework to address consumer disputes effectively.This study aims to deepen understanding of consumer rights and seller obligations in digital marketplaces. Employing a normative legal research method, it analyzes relevant consumer protection legislation. The findings indicate that consumers have access to dispute resolution through the Consumer Dispute Resolution Agency (Badan Penyelesaian Sengketa Konsumen – BPSK). To strengthen legal protection in online transactions, enhanced oversight of business actors and public awareness‑raising regarding consumer rights are essential. Clear regulations and effective dispute‑resolution mechanisms will better safeguard consumers against unfair commercial practices.